Decentralization and Community Welfare : Lesson Learnt From Indonesia and The Case of Special Autonomy of Papua - Pius Suratman Kartasasmita (Centre for Public Policy and Management Studies, 2014)
Decentralization refers to a commonly accepted meanings of reversing the concentration of administration at a single center and conferring powers of local government. Therefore, it is regarded as a political phenomenon capturing delegation of power to lower level of government. The main objective of decentralization is to create the most efficient and accountable form of government possible. Three forms of decentralization are recognised, deconsentration, delegation and devolution. The claims of this article, first of all, is to advocate social accounts at explainning the level of community welfare across communities. Having discussed theoretical as well as empirical accounts on the relationship between decentralization policy and community welfare, it is concluded that such relationship is inconclusive and ambigue. The case of Special Autonomy of Papua demonstrate an extreme case of paradoxical decentralization policy aimed to foster welfare for local people in particular the welfare of indigenoeous Papuans.Despite the fact of inclusive results and ambiguity, it also reveals that many studies strongly indicated that dicentralization policy predict improvement of community welfare at least through four mechanism, such as fiscal capacity, administrative capacity, institutional design of policies and the role of local political leadership. Given that all, this article finally comes to five recommendations. Firstly, tohave a closer and serious attention on social accounts that works at mediating any technical organization including decentralization policy. Secondly, to take rigorous measures on local community welfare both objective as well as subjective measures. Thirdly, to articulate the need for rigorous measure on performance of local government using both an official local government performance measurement system such as EKPPD, EDOB and EKPOD as well as an internationally accepted measures such as ISO, CAF and the like. Fourtly, to continue applying community development strategy as well as enforcing greater roles of Civil Society Organizations (CSOs). Finally, to recommend the need for more systematic research agenda and rigorous assesment on both theoretical ground type of research as well as applied policy type of research that employs both quantitative and qualitative approach as well as comparative study and case study in order to make decentralization works for improving welfare across communities.Keywords: decentralization, social accounts, community welfare, stuctural mediation, Papua.